Intrusive rumination and academic burnout among adolescents in ethnic minority areas of China during the COVID-19 pandemic: PTSS as mediator and cognitive reappraisal as moderator - Linhui He; Xiaojiao Yuan; Qiuyan Chen; Xiaogang Wang (BMC, 2023)
Abstract Background The COVID-19 pandemic has had a significant negative impact on public health, prompting scholarly research in related fields. In this context, the present study reveals the psychological characteristics of adolescents in ethnic minority areas of China approximately five months after the 2020 outbreak of the COVID-19 pandemic, explores the relationship between intrusive rumination and academic burnout, and examines the role of post-traumatic stress symptoms (PTSS) and cognitive reappraisal in the relationship to provide an empirical foundation for developing effective psychological interventions for adolescents in the wake of the pandemic. Methods Based on cluster sampling, 941 middle school students (65.36% female, 74.71% senior high, Mage=15.95) in ethnic minority areas of China were surveyed using the Event Related Rumination Scale, Adolescent Academic Burnout Scale, Post-traumatic Stress Checklist Scale, Emotion Regulation Strategy Scale, and a self-designed demographic questionnaire. Results During the COVID-19 pandemic, 7.44% of Chinese ethnic minority adolescents in our study sample were classified as PTSD positive, and 10.95% exhibited partial PTSD. Intrusive rumination significantly predicted academic burnout, and PTSS played a key mediating role between the two, accounting for 58.51% of the total effect. After controlling for PTSS, cognitive reappraisal moderated the effects of intrusive rumination on academic burnout. Specifically, the effect of intrusive rumination on academic burnout decreased with improvement in cognitive reappraisal. Conclusions Intrusive rumination indirectly affected academic burnout in adolescents through PTSS as a crucial mediator, and the remnant direct effect was alleviated by cognitive reappraisal. This finding emphasises the importance of adopting a comprehensive approach that encompasses cognitive, emotional, and physiological symptoms to understand and address academic burnout among adolescents during the COVID-19 pandemic.